Organizational propaganda on the Internet: A systematic review. (January 2020) - Lock, Irina; Ludolph, Ramona
The digital environment alters the way organizations use propaganda and facilitates its spread. This development calls for an outline of the features of propaganda by organizations on the Internet and to reconsider where public relations (PR) stops and propaganda begins. By means of a systematic review of primary research on organizational propaganda online, we propose a definition and describe the 'five Ws' of digital organizational propaganda: who employs propaganda, to whom, on which channels, which media are used (where), the objectives of the propaganda strategy (why), and in which contexts it occurs (when). Contrary to the offline setting, organizations engaging in propaganda online do not hide their identity and primarily address (potential) followers with the goal to change attitudes. Based on our findings, we propose a classification of digital organizational propaganda along three dimensions: ethical versus unethical, mutual understanding versus persuasion, and direct versus indirect communication. Digital organizational propaganda is defined as the direct persuasive communicative acts by organizations with an unethical (i.e. untruthful, inauthentic, disrespectful, or unequal) intent through digital channels. Thus, this study addresses the imbalance between the growing primary research on digital propaganda, the missing definition, and the lacking systematic empirical overview of propaganda's digital characteristics.